2012
DOI: 10.5402/2012/707329
|View full text |Cite
|
Sign up to set email alerts
|

Phimosis in Children

Abstract: Phimosis is nonretraction of prepuce. It is normally seen in younger children due to adhesions between prepuce and glans penis. It is termed pathologic when nonretractability is associated with local or urinary complaints attributed to the phimotic prepuce. Physicians still have the trouble to distinguish between these two types of phimosis. This ignorance leads to undue parental anxiety and wrong referrals to urologists. Circumcision was the mainstay of treatment for pathologic phimosis. With advent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 69 publications
1
32
0
1
Order By: Relevance
“…This together with intermittent erections results in resolution of phimosis over time. 3,6,7,10 Present study has attempted to simplify the approach towards physiological phimosis. It is to be emphasized that no interventions or surgery should be advised in these young patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This together with intermittent erections results in resolution of phimosis over time. 3,6,7,10 Present study has attempted to simplify the approach towards physiological phimosis. It is to be emphasized that no interventions or surgery should be advised in these young patients.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have elaborated the role of circumcision in phimosis. 3,4 However, these are valid only for the pathological variant with some predisposing factor. The factors might be balanitis, smegma, paraphimosis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors [1][2][3][4] have advocated this, often providing guidelines and time schedules for different interventions, if required. Circumcision, as a choice of care, has been practiced for over 5000 years; despite the challenges and arguments against and for, it is currently practiced in all the provinces and territories of Canada at varying prevalence rates.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of medical records carried out in England and Western Australia revealed that medically indicated circumcisions were seven times more than the expected incidence of phimosis in children less than 15 years of age. 2 Undescended testis is present in about 1-4.5% of newborns with a higher incidence in preterms (30-45%). In infants born with undescended testes, the testes may descend into the scrotum in 75% of full-term neonates and in 90% of premature newborn boys in infancy, and the incidence decreases to 0.8-1.2% at 1 year of age.…”
Section: Introductionmentioning
confidence: 99%